Method for preparing alkaline anion exchange membrane through in-situ crosslinking

Preparation of alkaline anion exchange membrane by in-situ crosslinking solves the problems of low ionic conductivity and poor stability, and achieves high-performance applications in hydrogen electrolyzed water, especially under low alkali concentration and high voltage conditions. Good electrochemical properties and long-term stability.

CN119215696APending Publication Date: 2024-12-31JIANGSU WEIDAO ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411453921.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The alkaline anion exchange membrane has a low ion conductivity and poor stability under high voltage conditions, which limits its application in hydrogen electrolyzed water.

Method used

In situ crosslinking preparation method, by mixing the solution of polyvinyl alcohol and chitosan with quaternary ammonium salts and adding crosslinking agents, natural drying and physical heat crosslinking are carried out to form alkali with high ionic conductivity and mechanical stability. Anion exchange membrane.

Benefits of technology

Improves the ionic conductivity and mechanical stability of the alkali anion exchange membrane, can operate stably under low alkali concentration and high voltage conditions, the current density reaches 550mA cm-2, and remains stable for more than 50 hours during long-term tests. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215696A_ABST
    Figure CN119215696A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing an alkaline anion exchange membrane by in-situ crosslinking, which comprises the following steps: (1) mixing a polyvinyl alcohol solution and a chitosan solution, and then adding a quaternary ammonium salt solution to obtain a homogeneous solution; (2) adding a cross-linking agent into the homogeneous solution, and naturally drying the solution to form a film to obtain a precursor film; and (3) carrying out physical thermal crosslinking on the precursor membrane, and finally dipping the precursor membrane in an alkaline solution for ion exchange to obtain the alkaline anion exchange membrane. The in-situ cross-linked alkaline anion exchange membrane provided by the invention has relatively high ionic conductivity and good stability, the raw materials are green and environment-friendly and low in price, the in-situ cross-linking method is simple and efficient, and the in-situ cross-linked alkaline anion exchange membrane shows good performance in the application of the alkaline anion exchange membrane to electrolyzed water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen energy, and particularly relates to a method for preparing an alkaline anion exchange membrane by in-situ cross-linking. Background Art

[0002] Hydrogen is not only an important energy carrier, but also an important chemical raw material. It is widely used in energy storage, chemical smelting and other aspects. According to the different carbon emissions, hydrogen technology can be divided into three types: 1) Hydrogen produced using fossil energy such as coal and natural gas is called "gray hydrogen"; 2) Hydrogen produced by steam methane reforming or autothermal steam reforming of natural gas is called "blue hydrogen"; 3) Hydrogen produced by electrolyzing water through renewable energy is called "green hydrogen". At present, only a small part of hydrogen is produced by water electrolysis, and more hydrogen still mainly relies on the traditional chemical industry. In the context of "dual carbon", in order to achieve true "zero carbon emissions", "green hydrogen" technology should be vigorously developed.

[0003] Low-temperature water electrolysis is an environmentally friendly and efficient technology for producing high-purity hydrogen. Low-temperature water electrolysis technology is mainly divided into three types: alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEMWE) and anion exchange membrane water electrolysis (AEMWE). Among them, the structure of anion exchange membrane water electrolysis (AEMWE) technology is similar to that of PEM electrolyzer. The AEMWE device can use pure water or low-concentration alkaline solution as electrolyte, effectively avoiding the problem of strong alkali corrosion, and has the advantages of no leakage, small size, and easy handling, showing good application prospects. In addition, the weak alkaline operating environment of AEMWE can combine the advantages of traditional AWE, and has the characteristics of electrodes composed of non-precious metal catalysts such as transition metal oxides and hydroxides, which greatly saves its cost. However, due to the limited migration efficiency of hydroxide ions, anion exchange membranes (AEMs) usually exhibit low ionic conductivity. In particular, under high voltage and current operating conditions, their stability is poor. Therefore, there is still an urgent need to develop new AEMs with good ionic conductivity and high stability to improve the performance of AEMWE. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing an alkaline anion exchange membrane by in-situ crosslinking, so as to solve the technical problems of low ion conductivity of the alkaline anion exchange membrane and poor stability in electrolyzed water of the alkaline anion exchange membrane.

[0005] The present invention provides a method for preparing an alkaline anion exchange membrane by in-situ cross-linking, comprising the following steps:

[0006] (1) mixing a polyvinyl alcohol solution and a chitosan solution, and then adding a quaternary ammonium salt solution to obtain a homogeneous solution;

[0007] (2) adding a crosslinking agent to the homogeneous solution, and naturally drying the solution to form a film to obtain a precursor film;

[0008] (3) The precursor membrane is subjected to physical thermal cross-linking and finally immersed in an alkaline solution for ion exchange to obtain an alkaline anion exchange membrane.

[0009] Preferably, the molecular weight of the polyvinyl alcohol in step (1) is 89,000-98,000.

[0010] Preferably, the mass concentration of the polyvinyl alcohol solution in step (1) is 10%-15%; the mass concentration of the chitosan solution is 5%-8%; and the mass ratio of the polyvinyl alcohol to chitosan is 1:0.5-1.

[0011] Preferably, the quaternary ammonium salt in step (1) is guar gum hydroxypropyltrimethylammonium chloride; the mass ratio of the quaternary ammonium salt to the total mass of the polyvinyl alcohol and chitosan is 1:1.

[0012] Preferably, the cross-linking agent in step (2) is glutaraldehyde, and the amount added is 0.5%-10% of the total mass of the components in the homogeneous solution. More preferably, the amount added is 2% of the total mass of the components in the homogeneous solution.

[0013] Preferably, the physical heat crosslinking temperature in step (3) is 110-150°C, and the time is 30-150 min. More preferably, the physical heat crosslinking temperature is 120°C, and the time is 60 min.

[0014] Preferably, the alkaline solution in step (3) is a KOH solution with a molar concentration of 1-2 mol / L.

[0015] Preferably, the ion exchange time in step (3) is 24-48 hours.

[0016] Furthermore, the alkaline anion exchange membrane obtained in step (3) is used in alkaline anion exchange membrane water electrolysis.

[0017] Beneficial Effects

[0018] (1) The present invention adopts a dual-skeleton strategy and introduces quaternary ammonium salt guar gum hydroxypropyltrimethylammonium chloride to form interconnected hydrophilic nanochannels in the membrane, which can achieve rapid transport of hydroxide ions in a restricted and directional manner.

[0019] (2) The present invention optimizes the cross-linking strategy by effectively regulating the optimal physical thermal cross-linking temperature and adopting a more efficient and environmentally friendly in-situ chemical cross-linking, so that the membrane has higher ionic conductivity, better dimensional stability and mechanical stability.

[0020] (3) The alkaline anion exchange membrane of the present invention has good electrochemical performance in the application of AEM water electrolysis. In particular, the current density can reach 550 mA cm at low alkali concentration (1 M KOH), 80 ° C, and 2 V voltage. -2 , and can work stably for more than fifty hours in long-term stability tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The in-situ cross-linked alkaline anion exchange membrane PVA / CS-T prepared in Example 1 4,2 +GA 1% Compared with PVA / CS-T without adding crosslinker GA 4,2 +GA 0% SEM cross-sectional comparison of the membrane;

[0022] Figure 2 The in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T 1,2 +GA 1% 、PVA / CS-T 2,2 +GA 1% 、PVA / CS-T 3,2 +GA 1% 、PVA / CS-T 4,2 +GA 1% 、PVA / CS-T 5,2 +GA 1% )'s ionic conductivity and water content comparison chart;

[0023] Figure 3 The in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T) with different physical heat cross-linking temperatures prepared in Example 3 4,1 +GA 1% 、PVA / CS-T 4,2 +GA 1% 、PVA / CS-T 4,3 +GA 1% 、PVA / CS-T 4,4 +GA 1% 、PVA / CS-T 4,5 +GA 1% )'s ionic conductivity and water content comparison chart;

[0024] Figure 4 The in-situ cross-linked alkaline anion exchange membranes (PVA / CS-T 4,2 +GA 0.5% 、PVA / CS-T 4,2 +GA 1%、PVA / CS-T 4,2 +GA 2% 、PVA / CS-T 4,2 +GA 5% 、PVA / CS-T 4,2 +GA 10% )'s ionic conductivity comparison chart;

[0025] Figure 5 The in-situ cross-linked alkaline anion exchange membranes (PVA / CS-T 4,2 +GA 0.5% 、PVA / CS-T 4,2 +GA 1% 、PVA / CS-T 4,2 +GA 2% 、PVA / CS-T 4,2 +GA 5% 、PVA / CS-T 4,2 +GA 10% )’s stress-strain comparison diagram;

[0026] Figure 6 The in-situ cross-linked alkaline anion exchange membrane PVA / CS-T prepared in Example 4 4,2 +GA 2% Polarization curve using nickel mesh as electrode at 80℃ and 1mol / L KOH;

[0027] Figure 7 The in-situ cross-linked alkaline anion exchange membrane PVA / CS-T prepared in Example 4 4,2 +GA 2% The stability of the electrode was tested at 60°C and 1 mol / L KOH using a nickel mesh. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0029] The microscopic morphology of the product of the embodiment of the present invention was tested by SEM (Hitachi S-4800), the conductivity of the membrane and the electrolysis of water related tests were carried out on an electrochemical workstation, and the mechanical properties of the membrane were characterized by an H5K-S material tester.

[0030] Example 1

[0031] This embodiment provides a method for preparing an in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T+GA), comprising the following steps:

[0032] Step 1): 10% polyvinyl alcohol (PVA) aqueous solution and 5% chitosan (CS) acetic acid solution in a mass ratio of 1:0.5 were placed in a beaker and mechanically stirred at 300 r / min for 30 min at room temperature to form a homogeneous solution.

[0033] Step 2) Take an appropriate amount of quaternary ammonium salt GG in deionized water, mechanically stir at 600 r / min at room temperature for 2 h to obtain a GG aqueous solution, slowly add it to the homogeneous solution obtained in step 1) to ensure that the mass ratio of the framework component to the quaternary ammonium salt is 1:1, and continue stirring at 300 r / min at room temperature for 20 h to obtain solution D.

[0034] Step 3): Add crosslinking agent GA to the solution D obtained in step 2), stir for 20 minutes, pour into a culture dish, and dry naturally to form a film. The content of GA is 1% of the total mass of the components in the solution.

[0035] Step 4) The precursor membrane prepared in step 3) was peeled off from the culture dish, subjected to physical thermal crosslinking at 120°C for 60 min, and finally immersed in 1 mol / L KOH solution for 24 h for ion exchange to obtain an in-situ crosslinked alkaline anion exchange membrane (PVA / CS-T 4,2 +GA 1% ), its specific appearance is as follows Figure 1 shown.

[0036] Example 2

[0037] This embodiment provides a method for preparing an in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T+GA), comprising the following steps:

[0038] Step 1): 10% polyvinyl alcohol (PVA) aqueous solution and 5% chitosan (CS) acetic acid solution in a mass ratio of 1:0.5 were placed in a beaker and mechanically stirred at 300 r / min for 30 min at room temperature to form a homogeneous solution.

[0039] Step 2) Take an appropriate amount of quaternary ammonium salt GG in deionized water, mechanically stir at 600 r / min at room temperature for 2 h to obtain a GG aqueous solution, slowly add it to the homogeneous solution obtained in step 1) to ensure that the mass ratio of the framework component to the quaternary ammonium salt is 1:1, and continue stirring at 300 r / min at room temperature for 20 h to obtain solution D.

[0040] Step 3): Add the crosslinking agent GA to the solution D obtained in step 2), stir for 20 minutes, and then immediately pour it into a culture dish and dry it naturally to form a film. The content of GA is 1% of the total mass of the components in the solution.

[0041] Step 4) The precursor membrane prepared in step 3) was peeled off from the culture dish, placed in an oven at 120°C, and subjected to physical thermal crosslinking for different crosslinking times (30 min, 60 min, 90 min, 120 min, 150 min). Finally, the membrane was immersed in a 1 mol / L KOH solution for 24 h for ion exchange to obtain an in-situ crosslinked alkaline anion exchange membrane (PVA / CS-T 1,2 +GA 1% 、PVA / CS-T 2,2 +GA 1% 、PVA / CS-T 3,2 +GA 1% 、PVA / CS-T 4,2 +GA 1% 、PVA / CS-T 5,2 +GA 1% ).

[0042] Example 3

[0043] This embodiment provides a method for preparing an in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T+GA), comprising the following steps:

[0044] Step 1): 10% polyvinyl alcohol (PVA) aqueous solution and 5% chitosan (CS) acetic acid solution in a mass ratio of 1:0.5 were placed in a beaker and mechanically stirred at 300 r / min for 30 min at room temperature to form a homogeneous solution.

[0045] Step 2) Take an appropriate amount of quaternary ammonium salt GG in deionized water, mechanically stir at 600 r / min at room temperature for 2 h to obtain a GG aqueous solution, slowly add it to the homogeneous solution obtained in step 1) to ensure that the mass ratio of the framework component to the quaternary ammonium salt is 1:1, and continue stirring at 300 r / min at room temperature for 20 h to obtain solution D.

[0046] Step 3): Add the crosslinking agent GA to the solution D obtained in step 2), stir for 20 minutes, and then immediately pour it into a culture dish and dry it naturally to form a film. The content of GA is 1% of the total mass of the components in the solution.

[0047] Step 4) The precursor membrane prepared in step 3) was peeled off from the culture dish, and after 60 min, the membrane was physically cross-linked at different temperatures (110°C, 120°C, 130°C, 140°C, and 150°C), and finally the membrane was immersed in a 1 mol / L KOH solution for 24 h for ion exchange to obtain an in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T 4,1 +GA 1% 、PVA / CS-T 4,2 +GA 1% 、PVA / CS-T 4,3+GA 1% 、PVA / CS-T 4,4 +GA 1% 、PVA / CS-T 4,5 +GA 1% ).

[0048] Example 4

[0049] This embodiment provides a method for preparing an in-situ cross-linked alkaline anion exchange membrane (PVA / CS-T+GA), comprising the following steps:

[0050] Step 1): 10% polyvinyl alcohol (PVA) aqueous solution and 5% chitosan (CS) acetic acid solution in a mass ratio of 1:0.5 were placed in a beaker and mechanically stirred at 300 r / min for 30 min at room temperature to form a homogeneous solution.

[0051] Step 2) Take an appropriate amount of quaternary ammonium salt GG in deionized water, mechanically stir at 600 r / min at room temperature for 2 h to obtain a GG aqueous solution, slowly add it to the homogeneous solution obtained in step 1) to ensure that the mass ratio of the framework component to the quaternary ammonium salt is 1:1, and continue stirring at 300 r / min at room temperature for 20 h to obtain solution D.

[0052] Step 3): Add crosslinking agent GA to the solution D obtained in step 2), stir for 20 minutes, pour into a culture dish, and dry naturally to form a film. The content of GA is (0.5%, 1%, 2%, 5%, 10%) of the total mass of the components in the solution.

[0053] Step 4) The precursor membrane prepared in step 3) was peeled off from the culture dish, subjected to physical thermal crosslinking at 120°C for 60 min, and finally immersed in 1 mol / L KOH solution for 24 h for ion exchange to obtain an in-situ crosslinked alkaline anion exchange membrane (PVA / CS-T 4,2 +GA 0.5% 、PVA / CS-T 4,2 +GA 1% 、PVA / CS-T 4,2 +GA 2% 、PVA / CS-T 4,2 +GA 5% 、PVA / CS-T 4,2 +GA 10% ).

[0054] like Figure 1 As shown, PVA / CS-T 4,2 +GA 0% There are a lot of concave wrinkles on the cross section, but PVA / CS-T 4,2 +GA 1%The degree of wrinkle depression is reduced and the cross section is smoother. The above results show that under the action of crosslinker GA, the compatibility between the components is improved. At the same time, strong intermolecular forces are formed between -NH2 and -OH in chitosan and -OH in PVA, which effectively supports the internal structure of the membrane.

[0055] like Figure 2 As shown in Figure 2, when the physical thermal crosslinking time is 60 min, the membrane has a higher conductivity while maintaining a lower water content.

[0056] like Figure 3 As shown in the figure, with the increase of thermal cross-linking temperature, the conductivity and moisture content of the membrane both show a downward trend. Excessive thermal cross-linking will take away too much moisture, causing the skeleton network structure to collapse and the amorphous region to recrystallize, which is not conducive to ion transport. Therefore, after comprehensive consideration, the thermal cross-linking conditions are selected as 120°C, 60min.

[0057] like Figure 4 As shown in the figure, with the deepening of in-situ crosslinking degree, the OH - The conductivity shows a gradually increasing trend.

[0058] like Figure 5 As shown in the figure, as the degree of crosslinking increases, the elongation at break of the film shows a downward trend, while the strength first increases and then decreases. This is because the hydrogen bonds between the PVA main chain and the CS main chain are gradually replaced by covalent bonds as the degree of crosslinking increases. Hydrogen bonds can dissipate energy through dynamic breaking and reorganization during strain, and this flexibility is not possessed by covalent bonds. Therefore, when too many covalent bonds are formed in the film, the mechanical properties of the film will be seriously affected. Considering all factors, PVA / CS-T was selected. 4,2 +GA 2% The membrane is used in alkaline anion exchange membrane water electrolysis test.

[0059] like Figure 6 As shown, with nickel mesh as the electrode, the current density at 2V in 1 mol KOH electrolyte at 80°C is 550 mA cm -2 .

[0060] like Figure 7 As shown, nickel mesh was used as the electrode at a current density of 200 mA cm -2 In the 1 mol / L KOH electrolyte at 60°C, it can work stably for more than 50 hours, indicating that the in-situ cross-linked alkaline anion exchange membrane exhibits good stability in the application of AEMWE device.

[0061] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention in any form or substance. It should be noted that a person skilled in the art may make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be considered as the protection scope of the present invention.

Claims

1. A method for preparing an alkaline anion exchange membrane by in-situ cross-linking, comprising the following steps: (1) mixing a polyvinyl alcohol solution and a chitosan solution, and then adding a quaternary ammonium salt solution to obtain a homogeneous solution; (2) adding a crosslinking agent to the homogeneous solution, and naturally drying the solution to form a film to obtain a precursor film; (3) The precursor membrane is subjected to physical thermal cross-linking and finally immersed in an alkaline solution for ion exchange to obtain an alkaline anion exchange membrane.

2. The method according to claim 1, characterized in that: The molecular weight of the polyvinyl alcohol in the step (1) is 89,000-98,000.

3. The method according to claim 1, characterized in that: The mass concentration of the polyvinyl alcohol solution in step (1) is 10%-15%; the mass concentration of the chitosan solution is 5%-8%; the mass ratio of the polyvinyl alcohol to chitosan is 1:0.5-1.

4. The method according to claim 1, characterized in that: The quaternary ammonium salt in step (1) is guar gum hydroxypropyltrimethylammonium chloride; the mass ratio of the quaternary ammonium salt to the total mass of the polyvinyl alcohol and chitosan is 1:

1.

5. The method according to claim 1, characterized in that: The cross-linking agent in step (2) is glutaraldehyde, and the amount added is 0.5%-10% of the total mass of the components in the homogeneous solution.

6. The method according to claim 1, characterized in that: The physical heat crosslinking temperature in step (3) is 110-150° C. and the time is 30-150 min.

7. The method according to claim 1, characterized in that: The alkaline solution in step (3) is a KOH solution with a molar concentration of 1-2 mol / L.

8. The method according to claim 1, characterized in that: The ion exchange time in step (3) is 24-48 hours.

9. The method according to claim 1, characterized in that: The alkaline anion exchange membrane obtained in the step (3) is used in alkaline anion exchange membrane electrolysis of water.

Citation Information

Cited By

  • Quaternization synergistic metal coordination chitosan-based anion exchange membrane and preparation method thereof

    CN121914431A